Political Program at Croatian Public TV: The Socio-Demographic Profiles of Viewers - Vukelić, Anton; Korenčić-Kampl, Konstanca; Bakić-Tomić, Ljubica (2006)
Abstract Because of the social turmoil on the territories of ex-Yugoslavia, politics has for 15 years been a dominant theme. On the basis of Milbrath classification of the political participation, the goal was to detect social groups of Croatian society which are even nowadays participating in greater extent in political contents. As an indicator we used data on everyday viewing of TV broadcasts with political profile (political program ratings) through sophisticated method of average minute rating (AMR). AFF index shows the ratio between the proportions of specific socio-demographic groups between viewers of a particular part of program and their share in population. In this research selected socio-demographic groups (older, less educated and middle class) do not correlate with Milbrath groups. Detailed analyses particularly in age groups indicate that the structure of viewers of broadcasts with political character equals to the structure of viewers of other broadcasts from prime time and TV program in whole. This data indicate nonselective watching of TV of part of TV population for analyzed broadcasts.
ENG